Systems Biology of Tumor Dormancy - Enderling, Heiko; Almog, Nava; Hlatky, Lynn (Advances in Experimental Medicine and Biology,, 2013)
This volume is based on the Workshop on Systems Biology of Tumor Dormancy meeting, held July 25th to July 28th, 2011. The first annual CCSB workshop brought together biologists, clinicians, mathematicians, and computer scientists to discuss various aspects of tumor dormancy and develop novel mathematical/computational models with the keynote speakers. Specific topics included the angiogenic switch, immune system interactions, cancer stem cells and signaling.